Design, Implementation, and Studying Efficiency of Peristaltic Pumps Roller for Kidney Failure - finjan, Saisban Lateef; Jabr, Abu al-Hassan Abd al-Wahhab; Hassan, Lec. Dr. Suhair Mohammed; Jam, Ass. Lec. Huda Farooq (Journal of Science in Medicine and Life, 2024)
The purpose of this project is to Design, implementation, and studying efficiency of peristaltic pumps roller for kidney failure. Outcomes of the design process involves, learning how to design and how to successfully design and implement of the system. The project system consists of switching power supply 5VDC 4A DC and L298N motor drive controller board module dual h Bridge DC Bipolar stepper motor. Safety unit is performed by using air bubble sensor which is used to stop the motor in case of bubble insertion. The IR sensor used which is consists of photo diode and photo transistor to detect the bubble and these components are connected to LM358 operation amplifier to detect bubble, stop motor and alarm user at the same time by the buzzer in ON state. Software of PIC12F675 is used as a microcontroller designed to control speed of motor driver and to stop motor in case of air bubble passing. The Performance of project system is experimentally tested by sensitivity and overall accuracy evaluation depending upon the classification models of true positive [TP], false positive [FP], true negative [TN], and false negative [FN]. Values of 99% sensitivity and 98.5% of overall accuracy are reflected to high efficiency in fabrication process of project system.